IMPLEMENTASI ASPEK-ASPEK KESEHATAN DAN KESELAMATAN KERJA (K3) PERKANTORAN DI INSTANSI X: IMPLEMENTATION OF ASPECTS IN OFFICE HEALTH AND SAFETY (K3) IN INSTANCES X - Tisna, Nur Sri; Yogisutanti, Gurdani; Hotmaida, Linda (JURNAL TERAS KESEHATAN, 2024)
Office Occupational Health and Safety (OHS) is important to implement because offices have potential hazards and risks. This study aims to analyze the implementation of office OHS aspects at X Office. This research uses a descriptive qualitative method, which collects data through observation, document analysis and interviews related to aspects of Office OHS, namely Policy, Safety, Health, Ergonomics, and Work Environment aspects. The collected data were analyzed using the triangulation method, namely comparing data from observations and interviews with Office OHS standards, as well as observation results compared to interviews and related documents. Data were analyzed through three stages, namely data reduction, data display, conclusion-drawing, and membercheck. Based on the results of the study, the socialization and application of OSH aspects in X Office is still not optimal. Policy aspects related to OHS are still at the draft stage and have not been fully implemented. Safety aspects,